The Book of Revival of Grammar (Ibrahim Mustafa) - Study, analysis and criticism - (Journal of the College of Basic Education, 2023)
((Say, if the sea were a supply of ink for the words of my Lord, the sea would have exhausted before the words of my Lord had been exhausted.We have brought the like of it (Al-Kahf 109/109).May God bless the best of creation, Muhammad bin Abdullah, the master of the messengers and the seal of the prophets.And upon his family and his chosen companions until the Day of Judgment.But after...One of the most important problems facing teachers and learners is the method of teaching and learning.Arabic grammar, if there is a problem in the opinion of those who want to facilitate and renew this process.But in fact there is no problem. However, diving into the aspects of linguistic anomalies and irregularitiesAnd the grammatical complexity - make this process some difficulty, especially in grammar far fromThe Arabic Saliqa, and what the Arabs are accustomed to, and what the grammarians have achieved from far-fetched bases.For anomalies of grammatical evidence. Some dialects produced defects as well. thatThe interest in those deviants has made the Arabic grammar foreign to the learners, who find it difficult.Where it is accepted and applied in the eloquent and common speech among the general speakers of the Arabic language.There is no doubt that the Noble Qur’an is the purifying pulp of Arabic, because it was revealed in the languagecommon to all Arab tribes, so he came eloquently expressing his understanding of the proximate and the far, containingAll linguistic and grammatical methods except Mandar, so it is considered the best helper for the study of the language.And dependent on the complexity of grammar and the application of grammatical and linguistic exercises, it is more appropriate to take its expressions